Low level wind forecast over the Uruguay River region nearby Gualeguaychú, using a boundary layer model forced by WRF regional operational forecasts - Salles, M. A. (2017)
The mesoscale atmospheric boundary layer model –BLM- is used to run daily low level wind field forecasts over the Uruguay River region nearby Gualeguaychú. BLM runs with a horizontal resolution of 1 km, forced by initial and boundary conditions defined from the operational WRF forecasts of the National Meteorological Service of Argentina at 5 km resolution. The low level wind forecast is validated with the observations of three 42-meter tall meteorological towers located on the coast of the Uruguay River, during the period June 2010 to May 2013. Despite the WRF forecast errors propagate and impact somehow the quality of the final forecast, BLM is able to overcome this situation and produce a forecast with smaller error than WRF at two of the three places.